2011
DOI: 10.1016/j.jtcvs.2010.08.063
|View full text |Cite
|
Sign up to set email alerts
|

The hemi-Mustard/bidirectional Glenn atrial switch procedure in the double-switch operation for congenitally corrected transposition of the great arteries: Rationale and midterm results

Abstract: We describe a 15-year experience with the double-switch operation using a modified atrial switch procedure with favorable midterm results. The risks of the hemi-mustard and bidirectional Glenn operation are minimal and are limited to a well-defined patient subset. The benefits include prolonged conduit life, reduced baffle- and sinus node-related complications, and technical simplicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 16 publications
0
50
0
Order By: Relevance
“…The substantial perioperative and late risks of banding and rebanding the pulmonary artery in ccTGA16 are accepted to gain the advantage of ultimately incorporating the LV into the systemic arterial circulation. Alternative surgical approaches to anatomic repair with the goal of addressing defects while establishing the LV as the systemic ventricle are Rastelli procedure with atrial switch, or a hemi-Mustard/bidirectional Glenn with arterial switch 17. A meta-analysis of 11 studies encompassing 124 patients suggested lower perioperative mortality with the Rastelli-type anatomic repair than with the other surgical approaches 18…”
Section: Surgical Optionsmentioning
confidence: 99%
“…The substantial perioperative and late risks of banding and rebanding the pulmonary artery in ccTGA16 are accepted to gain the advantage of ultimately incorporating the LV into the systemic arterial circulation. Alternative surgical approaches to anatomic repair with the goal of addressing defects while establishing the LV as the systemic ventricle are Rastelli procedure with atrial switch, or a hemi-Mustard/bidirectional Glenn with arterial switch 17. A meta-analysis of 11 studies encompassing 124 patients suggested lower perioperative mortality with the Rastelli-type anatomic repair than with the other surgical approaches 18…”
Section: Surgical Optionsmentioning
confidence: 99%
“…Finally, reduced mRV volume load would delay the timing of the RV-PA conduit change 19)20). Malhotra et al9) reported that only two revisions of the RV-PA conduit were performed among 25 patients who underwent the hemi-Mustard procedure at 11.6 and 12.4 years after the double switch operation during a median follow-up of 4.9 years (range:7 months-16 years). This shows that RV-PA conduit longevity is significantly improved by the hemi-Mustard procedure.…”
Section: Discussionmentioning
confidence: 99%
“…With accumulated experience and modification of procedures, the outcome of anatomic repair has improved 5)6)7)8). We have modified the Mustard procedure by adding a bidirectional cavopulmonary shunt (BCPS) in the atrial switch procedure (hemi-Mustard procedure) of anatomic repair in selected patients, as reported previously 9)10)…”
Section: Introductionmentioning
confidence: 96%
“…This strategy, which technically simplifi es the atrial switch operation, may decrease the risk of sinus arrhythmias and prolong conduit survival due to decreased fl ow secondary to the BDG [ 16 ]. The main drawbacks are the long-term moderate elevation of the SVC pressure, the need for a competent pulmonary valve, the inability to use transvenous access for pacing, and the impaired functional capacity of patients [ 15 ].…”
Section: Issues Related To the 1½ Mustard Proceduresmentioning
confidence: 99%